Ultrasensitive tactile sensors based on planar liquid crystal-gated-organic field-effect transistors with polymeric dipole control layers1. Issue 70 (31st July 2015) - Seo, Jooyeok; Song, Myeonghun; Han, Hyemi; Kim, Hwajeong; Lee, Joon-Hyung; Park, Soo-Young; Kang, Inn-Kyu; Kim, Youngkyoo
<x xml:space="preserve">Abstract</x> Liquid crystal-gated-organic field-effect transistors with polymeric dipole control layers can sense extremely low gas flows unfelt by human skins.